2011
DOI: 10.1093/jaoac/94.5.1447
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Validated Stability-Indicating High-Performance Liquid Chromatographic Method Using Photodiode Array Detection for Simultaneous Determination of Granisetron, Methylparaben, Propylparaben, Sodium Benzoate, and Their Main Degradation Products in Oral Pharmaceutical Preparations

Abstract: A simple, rapid, and sensitive RP-HPLC method using photodiode array detection was developed and validated for the simultaneous determination of granisetron hydrochloride, 1-methyl-1H-indazole-3-carboxylic acid (the main degradation product of granisetron), sodium benzoate, methylparaben, propylparaben, and 4-hydroxybenzoic acid (the main degradation product of parabens) in granisetron oral drops and solutions. The separation of the compounds was achieved within 8 min on a SymmetryShield RP18 column (100 × 4.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Parabens are widely present in foodstuffs, , cosmetics, and pharmaceuticals . Further, parabens have been reported to occur in indoor environments, wastewater treatment plant discharge and surface water .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parabens are widely present in foodstuffs, , cosmetics, and pharmaceuticals . Further, parabens have been reported to occur in indoor environments, wastewater treatment plant discharge and surface water .…”
Section: Introductionmentioning
confidence: 99%
“…2 Parabens are widely present in foodstuffs, 16,17 cosmetics, 18 and pharmaceuticals. 19 Further, parabens have been reported to occur in indoor environments, 20−22 wastewater treatment plant discharge and surface water. 23 In 2006, Ye et al 24 reported MeP and PrP in urine from U.S. adults (n = 100), at median concentrations of 43.9 and 9.1 ng/mL, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Extraction sorbents for on-line SPE extend to an array of media including large particles for turbulent flow chromatography, restricted access materials (RAM), monolithic materials and disposable cartridges utilizing traditional packing's such as those used in Spark Holland systems. In the end, this paper also discusses recent studies of matrix effect in LC-MS/MS analysis and how to reduce/eliminate matrix effect in method development and validation [32][33][34].…”
Section: Recent Advancement In Hplcmentioning
confidence: 99%
“…Various analytical methods were reported for quantitative determination of GRN in bulk, different pharmaceutical and biological samples, as spectrophotometric, 14,15 spectro-uorimetric, 16 HPTLC, 17,18 and HPLC [19][20][21][22] methods. Electrochemical techniques are widely used nowadays for their high sensitivity, selectivity, cost effective and high sample throughput within short analysis time.…”
Section: Introductionmentioning
confidence: 99%